METODE QIROATI SEBAGAI MODEL PEMBELAJARAN MEMBACA AL QUR`AN UNTUK TINGKAT SEKOLAH DASAR (PENELITIAN PADA SD IT AL ICHWAN CIKARANG UTARA BEKASI) - Agus Ruswandi (Balai Penelitian dan Pengembangan Agama Jakarta, 2019)
Studying the Qur'an is a must for every Muslim, because the Qur'an as a religious guide must be properly understood. Reading the Qur'an is not like reading other texts. In the Qur'an there are certain rules which if the rule is not used then the meaning of the Qur'an will be wrong. Therefore, there needs to be an innovative method in the study of the Qur'an, as it is known that in elementary school the subject of Islamic Education is only around 2-3 hours for a week. Al-Ichwan Elementary School is one of the schools that innovates by applying the Al-Qur'an reading method through the Qiroati method. The purpose of this research was to find out how the learning design model, the learning process, the form of evaluation, excellence, learning outcomes, and the problems and solutions in learning the Qur'an with the Qiroati method at Al-Ichwan Elementary School. This research uses a qualitative approach and the type of research uses descriptive analytical methods, with the aim of producing conceptual models of Al-Qur'an learning by applying the Qiroati method to the elementary school level. Data collection techniques through observation, interviews and documentation. To analyze the data used descriptive qualitative method, namely the description based on the symptoms that appear. In order for the assessment results to go well, the data analysis process is carried out by steps of data reduction, data display and conclusion drawing.